(untitled) (Docentes 2.0 Journal, 2024)
Research in early childhood education is a dynamic field that reflects educational policies, theoretical advances, and constantly evolving pedagogical practices. The objective of the study was to carry out a bibliometric analysis of the scientific production on early childhood education in Peru to identify trends and patterns that can inform researchers, pedagogues, and politicians in this sector based on theories such as educational change, analysis of public policies and critical theory of education. The research was based on the systematic method, humanistic paradigm, and qualitative approach, with topical narrative design and exploratory and longitudinal documentary type. Through a systematic bibliographic review and a bibliometric analysis in the Scopus database, this study synthesizes the trends in scientific production in early childhood education in Peru between 2018 and 2022. Of the 298 publications identified, patterns were extracted and cataloged according to year, international scope, discipline, and document type. The findings are visually articulated, revealing that medicine dominates with 131 studies, evidencing a surprising interdisciplinarity. Most works, equivalent to 75%, were disseminated through magazine articles. The data obtained focuses on the interpretation of the perspectives of various academics on teaching materials for preschool research, thus highlighting the most significant and frequent contributions in the analyzed corpus.